2021
DOI: 10.3390/jpm11090865
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Dysregulation, Temperament and Lifetime Suicidal Ideation among Youths with Mood Disorders

Abstract: Background: Psychopathological dimensions contributing to suicidal ideation in young age are poorly understood. We aimed to investigate the involvement of emotional dysregulation and temperament in suicide risk in a sample of accurately selected young patients with mood disorders and a matched sample of healthy controls (HC). Methods: We assessed 50 young patients (aged 14–25 years) with DSM-5 bipolar or depressive disorders for clinical and psychopathological characteristics and 82 age and sex, educational le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Patients with EUPD typically begin treatment around the age of 18, though symptoms often begin earlier, with 60% of those with EUPD self-harming age 17 or younger [ 14 ]. No precursor syndrome has been identified specific to personality disorders, rather emotional dysregulation appears to be a spectrum that correlates with self-harm and suicidal thoughts [ 15 ]. Longitudinal studies have shown that remission in EUPD is slow.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with EUPD typically begin treatment around the age of 18, though symptoms often begin earlier, with 60% of those with EUPD self-harming age 17 or younger [ 14 ]. No precursor syndrome has been identified specific to personality disorders, rather emotional dysregulation appears to be a spectrum that correlates with self-harm and suicidal thoughts [ 15 ]. Longitudinal studies have shown that remission in EUPD is slow.…”
Section: Discussionmentioning
confidence: 99%
“…Particular challenges when treating patients with bipolar disorder occur in patients with rapid cycling conditions, background dysregulated affective temperaments, a history of suicidality, as well as elderly patients (75)(76)(77)(78). Another problem resides in the frequent need for polypharmacy (79).…”
Section: Cariprazine Efficacy Across the Wide Range Of Symptoms Of Bipolar Disordermentioning
confidence: 99%
“…As a result, it was expected that facets of body investment (body image, body care, body protection, and body touch) [ 23 , 24 ] would play a role in the prediction of non-suicidal self-harming injuries (NSSI) and acquired capability for suicide and suicide attempts [ 23 , 25 ]. In the meantime, the current literature focused attention on the well-established association between self-harming and self-destructive behaviors and greater degrees of emotion dysregulation [ 26 , 27 , 28 ]. Emotion regulation refers to a complex array of processes and strategies for monitoring, evaluating, and adjusting emotional experiences in the short-term and dynamically over time to accomplish goals [ 29 ].…”
Section: Introductionmentioning
confidence: 99%